Optimization of Biodiesel and Biofuel Process - Luna, Diego; Pineda, Antonio; Estevez, Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Although the compression ignition (C.I.) engine, invented by Rudolf Diesel, was originally intended to work with pure vegetable oils as fuel, more than a century ago, it was adapted to be used with a fuel of fossil origin, obtained from oil. Therefore, there would be no technical difficulties in returning to the primitive design of using biofuels of renewable origin, such as vegetable oils. The main drawback is found in the one billion C.I. engines which are currently in use, which would have to undergo a modification in the injection system in order to adapt them to the higher viscosity of vegetable oils in comparison to that of fossil fuels. Thus, the gradual incorporation of biofuels as substitutes of fossil fuels is mandatory.